Bacterial epibiont communities of panmictic Antarctic krill are spatially structured. Issue 4 (15th January 2021) - Clarke, Laurence J.; Suter, Léonie; King, Rob; Bissett, Andrew; Bestley, Sophie; Deagle, Bruce E.
Abstract: Antarctic krill ( Euphausia superba ) are amongst the most abundant animals on Earth, with a circumpolar distribution in the Southern Ocean. Genetic and genomic studies have failed to detect any population structure for the species, suggesting a single panmictic population. However, the hyper‐abundance of krill slows the rate of genetic differentiation, masking potential underlying structure. Here we use high‐throughput sequencing of bacterial 16S rRNA genes to show that krill bacterial epibiont communities exhibit spatial structuring, driven mainly by distance rather than environmental factors, especially for strongly krill‐associated bacteria. Estimating the ecological processes driving bacterial community turnover indicated this was driven by bacterial dispersal limitation increasing with geographic distance. Furthermore, divergent epibiont communities generated from a single krill swarm split between aquarium tanks under near‐identical conditions suggests physical isolation in itself can cause krill‐associated bacterial communities to diverge. Our findings show that Antarctic krill‐associated bacterial communities are geographically structured, in direct contrast with the lack of structure observed for krill genetic and genomic data.